2013
DOI: 10.1039/c3dt50960e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterisation and evaluation of a novel copper-64 complex with selective uptake in EMT-6 cells under hypoxic conditions

Abstract: The radiometal (64)Cu is now widely used in the development of diagnostic imaging agents for positron emission tomography (PET). The present study has led to the development and evaluation of a novel chelating agent for (64)Cu: the new monothiourea tripodal ligand 1-benzoyl-3-{6-[(bis-pyridin-2-ylmethyl-amino)-methyl]-pyridin-2-yl}-thiourea (MTUBo). X-ray crystallographic analysis has shown this ligand forms a mononuclear complex with copper(II) and co-ordinates via a trigonal bipyramidal N4S array of donor at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 56 publications
1
27
0
Order By: Relevance
“…Larger SD across reconstructions observed with FBP algorithm for mean SUV max and mean T/B may reflect limitations of this algorithm ( 13 ), arising from applying available defaults and possible low count-rate statistics. As expected for each respective time frame and within each respective reconstruction algorithm, mean T/B >corresponding mean SUV max and the difference was statistically significant (p<0.0001 in all cases) ( 21 ).…”
Section: Discussionsupporting
confidence: 68%
“…Larger SD across reconstructions observed with FBP algorithm for mean SUV max and mean T/B may reflect limitations of this algorithm ( 13 ), arising from applying available defaults and possible low count-rate statistics. As expected for each respective time frame and within each respective reconstruction algorithm, mean T/B >corresponding mean SUV max and the difference was statistically significant (p<0.0001 in all cases) ( 21 ).…”
Section: Discussionsupporting
confidence: 68%
“…It is a neutral lipophilic molecule with a high cell membrane permeability and diffuses readily from the blood to surrounding cells. Once within the cell, it undergoes reduction only in hypoxic cells and becomes trapped intracellularly, but washes out rapidly from normal cells without any change (49). Copper has several positron-emitting radioisotopes which can be used.…”
Section: Hypoxia In Lung Cancermentioning
confidence: 99%
“…Clinical studies have shown that 64 Cu-ATSM PET is feasible in NSCLC and may play a role as a prognostic marker (37,(49)(50)(51)(52).…”
Section: Hypoxia In Lung Cancermentioning
confidence: 99%
“…Recent work by Knight et al . compared the hypoxia selectivity and stability of the novel copper complex 64 Cu‐MTUBo, based on a tripodal monothiourea ligand, with that of 64 Cu‐ATSM . Similar to 64 Cu‐ATSM, 64 Cu‐MTUBo showed hypoxia selectivity in vitro , but time‐activity curves revealed faster tumour uptake of 64 Cu‐ATSM in vivo .…”
Section: Tumour Imaging With 64cumentioning
confidence: 99%